A prospective randomized multicentre study of the impact of gallium‐68 prostate‐specific membrane antigen (PSMA) PET/CT imaging for staging high‐risk prostate cancer prior to curative‐intent surgery or radiotherapy (proPSMA study): clinical trial protocol. (3rd June 2018) - Hofman, Michael S.; Murphy, Declan G.; Williams, Scott G.; Nzenza, Tatenda; Herschtal, Alan; Lourenco, Richard De Abreu; Bailey, Dale L.; Budd, Ray; Hicks, Rodney J.; Francis, Roslyn J.; Lawrentschuk, Nathan
Abstract : Background: Accurate staging of patients with prostate cancer (PCa) is important for therapeutic decision‐making. Relapse after surgery or radiotherapy of curative intent is not uncommon and, in part, represents a failure of staging with current diagnostic imaging techniques to detect disease spread. Prostate‐specific membrane antigen (PSMA) positron‐emission tomography (PET)/computed tomography (CT) is a new whole‐body scanning technique that enables visualization of PCa with high contrast. The hypotheses of this study are that: (i) PSMA‐PET/CT has improved diagnostic performance compared with conventional imaging; (ii) PSMA‐PET/CT should be used as a first‐line diagnostic test for staging; (iii) the improved diagnostic performance of PSMA‐PET/CT will result in significant management impact; and (iv) there are economic benefits if PSMA‐PET/CT is incorporated into the management algorithm. Objectives and Methods: The proPSMA trial is a prospective, multicentre study in which patients with untreated high‐risk PCa will be randomized to gallium‐68‐PSMA‐11 PET/CT or conventional imaging, consisting of CT of the abdomen/pelvis and bone scintigraphy with single‐photon emission CT/CT. Patients eligible for inclusion are those with newly diagnosed PCa with select high‐risk features, defined as International Society of Urological Pathology grade group ≥3 (primary Gleason grade 4, or any Gleason grade 5), prostate‐specific antigen level ≥20 ng/mL or clinical stage ≥T3. Patients with negative, equivocal or oligometastatic disease on first line‐imaging will cross over to receive the other imaging arm. The primary objective is to compare the accuracy of PSMA‐PET/CT with that of conventional imaging for detecting nodal or distant metastatic disease. Histopathological, imaging and clinical follow‐up at 6 months will define the primary endpoint according to a predefined scoring system. Secondary objectives include comparing management impact, the number of equivocal studies, the incremental value of second‐line imaging in patients who cross over, the cost of each imaging strategy, radiation exposure, inter‐observer agreement and safety of PSMA‐PET/CT. Longer‐term follow‐up will also assess the prognostic value of a negative PSMA‐PET/CT. Outcome and Significance: This trial will provide data to establish whether PSMA‐PET/CT should replace conventional imaging in the primary staging of select high‐risk localized PCa, or whether it should be used to provide incremental diagnostic information in selected cases.